SMALL AND MEDIUM SIZED ENTREPRISES; GROWTH FACTORS - Gjini, Kladiola (European Scientific Journal, ESJ, 2014)
SMEs occupy an important role in most of economies. In Albania the SMEs represent 99.6% of all registered businesses, the share of the SME sector in GDP is 72.9% of GDP and the number of employees reaches the level of 71.4% of all workers. The SMEs are considered as a key factor for a stable economic environment to make lower the levels of the poverty in the country, to make an equal income distribution and to increase the employment rate. The impact of SMEs is visible in almost every field like finance, human resources management, retail, service industry, manufacturing and the agricultural sector. SMEs often offer specialized services/products in a more efficient manner rather than larger companies. This paper aims to contribute in finding some determinant factors related to SMEs growth and performance in a transition economy. Empirical researches argues that firm growth is measured not only from traditional factors of the firm (size and age), but also from specific factors including internal financing, future business plan, factor productivity. During the last five years the economic situation has been very unclear and uncertain. SMEs have experience the most challenging crisis. The 2013 is expected to be a positive year regarding the Small and Medium Sized Enterprises in Europe, i.e. turning point. The economists are hopeful, and are expecting an increase in the total employment by 0.3% and 1% increase in the value added. Considering the importance in all economies for recovery and development, SMEs growth is a crucial issue.